Model and Analysis of Multi Level Multi Frequency RF Rectifier Energy System for Low Power Supply Application Device - Budi Herdiana; Bobi Kurniawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Sustainable energy for the mobile electronic devices always needed during the energy storage batteries capacity in the mobile electronic devices are limited for a few hours for the usage time. To get a long lasting operating time from the mobile electronics equipment sets, the energy source should always be connected into the device. In this paper, we were proposed a charging energy method via wireless operation supply using the microwaves (RF) radiated by the air multi-frequency. The RF to DC rectifier circuit is a major component for changing the RF wave to an electronic current (DC). The Dickson models were used as an approach to superiority includes a simple series, low DC ripple factor, etc. The design, analysis, and the experimentation from the rectifier circuit have been conducted and presented in this paper. In the measurement, the mobile electronic devices placed at a distance about 5 meters from the energy source with the system voltage DC 3.7V, and have been obtained at the working frequency between 825 - 960MHz with the PCE values 12-33%, and a ripple factor of ± 0,01%. The charging time energy is needed about 4 hours at the research trial room, and about 11 hours outdoor had been observed. Based on these results, the wirelessly energy charging method for the mobile electronic devices is a potential methods to resolve the sustainable energy issue and the green technology supporting with the most programs.